Digital tools and self-administered home blood tests: A convergent mixed methods pilot study - Lana Hebib; Emelie Gustafson Hedov; Maria Storgärds; Peder af Geijerstam; Marie Löf; Jason HY Wu; Lisa Kastbom; Karin Rådholm (Digital Health)
Background Digital tools and self-administered home blood tests offer a flexible approach to research data collection, biological sample management, and informed consent but require evaluation in relevant study settings. This study explored user experiences with a web-based digital tool for trial management, symptom reporting, and home blood testing. Methods Forty-three middle-aged participants took part in a 12-week mixed-method study, using digital tools for trial management, self-reported health data, and self-administered glycated hemoglobin A1c home blood tests. Usability was assessed through the validated mHealth App Usability Questionnaire (MAUQ) with additional study-specific items. Every second participant completed a semi-structured interview, analyzed using qualitative content analysis. Results The MAUQ responses (scale 1–7) indicated that digital consent (94.7% agreed), and home blood tests (100% agreed) were well-received. However, finding information on digital tools was challenging (52.9% disagreed it was easy), and participants did not perceive the tools highly effective for managing health (52.9% disagreed they were helpful). Interviews with 20 participants reinforced these findings, emphasizing motivation, support, efficient resource use, and the importance of clarity, usability, safety, and security. Conclusion While self-administered blood tests and online consent were considered user-friendly, improvements are needed in digital tool navigation and information accessibility to enhance usability in decentralized trials, especially for participants who find them difficult or unhelpful.